Matte painting : d'artiste : digital artists master class. - Altiner, Alp, ....-; Cole, Dylan, ....-; Stoski, Chris, ....- (Adelaide : Ballistic, 2009)
Matte painting' is dedicated to showcasing and teaching the skills behind the art of digital matte painting. Leading Hollywood matte painters Alp Altiner, Dylan Cole and Chris Stoski bring readers through the matte painting techniques used to create breathtaking, photo-realistic sets and backdrops for film, television and video games. Matte Painting work for sequences in 'Star Wars - Revenge of the Sith' feature prominently, as does an impressive painting for the 'Lord of the Rings' trilogy. Each master artist presents their unique approaches through a series of step-by-step tutorials from concept to final painting. 'D'artiste - Matte painting' dedicates a section to each master artist, including a personal gallery, biography, up to 28 pages of tutorial content each and an invited artist gallery featuring 56 matte paintings from talented digital artists worldwide.